The Effect of Structured Swimming Training on Improving Motor Coordination and Physical Fitness of Elementary School Students - Kasmad, M. Rachmat; Saleh, Muhammad Syahrul (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aimed to analyze the effect of structured swimming training on improving motor coordination and physical fitness of students at SD Inpres Unggulan BTN Pemda Makassar. The study used a quasi-experimental design with a One Group Pretest–Posttest model, involving 20 students. The variables measured included motor coordination using the Alternate Hand Wall Toss Test and physical fitness components, namely VO₂max, muscle strength, and agility. The structured swimming training program was implemented for six weeks, twice weekly. The results showed significant improvements in all variables after the intervention. Motor coordination increased on average from 15.8 to 26.4. VO₂max increased from 28.5 to 34.2 ml/kg/min, muscle strength increased from 11.4 to 14.8 kg, and agility showed a time reduction from 14.2 to 12.6 seconds. A paired sample t-test showed a p-value <0.05 for all variables, indicating a significant effect of structured swimming training on motor coordination and physical fitness. The results of this study confirm that swimming, as a structured activity, can comprehensively improve students' motor skills and physical condition. Integrating swimming training into physical education is considered relevant for supporting the physical development of elementary school-aged children. Further research is recommended using a control group design and a longer intervention duration to strengthen the generalizability of the findings.